2020
DOI: 10.1186/s13223-020-00434-0
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin with the potential effect on allergic diseases

Abstract: Quercetin is a naturally occurring polyphenol flavonoid which is rich in antioxidants. It has anti-allergic functions that are known for inhibiting histamine production and pro-inflammatory mediators. Quercetin can regulate the Th1/ Th2 stability, and decrease the antigen-specific IgE antibody releasing by B cells. Quercetin has a main role in antiinflammatory and immunomodulatory function which makes it proper for the management of different diseases. Allergic diseases are a big concern and have high health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 49 publications
1
89
0
3
Order By: Relevance
“…Therefore, compounds that affect the function of keratinocytes will have therapeutic potential. Many studies have shown that natural ingredients, such as isoflavones, apigenin, quercetin, and chrysin, have very good pharmacological activities in this regard [ 9 , 10 , 11 , 12 , 13 , 14 ]. Neferine has been found to inhibit the production or release of inflammatory substances, cytokines, and chemokines in other tissues or cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compounds that affect the function of keratinocytes will have therapeutic potential. Many studies have shown that natural ingredients, such as isoflavones, apigenin, quercetin, and chrysin, have very good pharmacological activities in this regard [ 9 , 10 , 11 , 12 , 13 , 14 ]. Neferine has been found to inhibit the production or release of inflammatory substances, cytokines, and chemokines in other tissues or cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that quercetin inhibits the secretion of harmful chemical mediators, including histamine, leukotrienes, major basic protein, and eosinophil cationic protein from mast cells and eosinophils in vitro and in vivo [ 14 , 15 ]. Furthermore, the influence of quercetin on the production of T-cell cytokines was investigated using an asthmatic mouse model, and it was reported that quercetin could reduce the increased levels of IL-4, and increased IFN-γ levels in bronchoalveolar lavage fluid after antigenic challenge via the modulation of T-box protein expressed in T cells (T-bet) and GATA-3 gene expression, resulting in significant attenuation of all asthmatic reactions [ 16 , 17 ]. Although these reports strongly suggest that quercetin is a good candidate as a supplement for modulation of allergic diseases, including AR, the mechanisms of the therapeutic action of quercetin on allergic responses is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical companies are involved in manufacturing supplements purported for use in asthma such as quercetin and pycnogenol [93]. Quercetin is one of the most natural polyphenolic antioxidants found in many food products, which exerts anti-allergic effects by suppressing airway hyperresponsiveness and eosinophil chemoattractants induced by periostin, leading to reduced risk of asthma and allergic diseases [94]. Pycnogenol (French Pinus pinaster) is a natural plant extract contains polyphenolic compounds capable of reducing asthma by inhibiting pro-inflammatory cytokine production [95].…”
Section: Data Applications and Influencesmentioning
confidence: 99%